2019
DOI: 10.3390/biom9010027
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis and Characterization of a Novel α-1→6-Glucosyl Rebaudioside C Derivative Sweetener

Abstract: Zero-calorie high-intensity sweeteners from natural sources perform very well in the market place. This has encouraged food scientists to continue the effort to search for novel natural ingredients to satisfy consumer demand. Rebaudioside C (reb C) is the third most prevalent steviol glycoside in the leaves of the Stevia rebaudiana Bertoni plant, but has limited applications in food and beverage products due to its low sweetness and high lingering bitterness compared to other major steviol glycosides, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Prakash et al (used UGTs with UDP-glucose) ,, and Gerwig, te Poele, Devlamynck, and Yang et al , (used glucansucrase enzyme with sucrose as glucosyl donor) determined structures of the synthetic products using a full set of NMR and MS analyses. However, although most industrial manufacturers produce glucosyl steviol glycosides with CGTase Toruzyme 3.0 L (a commercial cyclodextrin glycosyl transferase), the linkage pattern of GSGs obtained from CGTase still remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Prakash et al (used UGTs with UDP-glucose) ,, and Gerwig, te Poele, Devlamynck, and Yang et al , (used glucansucrase enzyme with sucrose as glucosyl donor) determined structures of the synthetic products using a full set of NMR and MS analyses. However, although most industrial manufacturers produce glucosyl steviol glycosides with CGTase Toruzyme 3.0 L (a commercial cyclodextrin glycosyl transferase), the linkage pattern of GSGs obtained from CGTase still remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has a low sweetness and a bitter aftertaste that affect the taste of food and beverages. Thus, its application is limited ( Yang et al, 2019 ). Previous studies have found that many glycosylation-modified products of all steviol glycosides have better sweetness and taste profiles ( Hellfritsch et al, 2012 ; Wan, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Physicochemical characterization indicated the formation of inclusion complexes with cyclodextrin which were shown to be an effective and promising alternative to enhance the anti-inflammatory activity and safety of this triterpene. Bioactive diterpenes were also described in this Special Issue: a review and an antitumor study with cembranoids from tobacco [15,16], and glucoside derivative rebaudioside C, a sweetener [17].…”
mentioning
confidence: 99%
“…Bioactive diterpenes were also described in this Special Issue: a review and an anti-tumor study with cembranoids from tobacco [ 15 , 16 ], and glucoside derivative rebaudioside C, a sweetener [ 17 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation